Recent Advancements of Porphyrin‐Like Single‐Atom Catalysts: Synthesis and Applications. Issue 6 (24th March 2021) - Yang, Hongzhou; Shi, Run; Shang, Lu; Zhang, Tierui
Abstract : Porphyrin, an active center in many biological enzymes, is an important environment‐friendly biomimetic catalyst, which shows high catalytic efficiency and selectivity. However, porphyrin has the disadvantages of decomposition, self‐polymerization and deactivation in catalysis, and unrecyclability in homogeneous catalysis, which limit its wide application in catalysis. With the development of single‐atom catalysis, it is found that porphyrin‐like single‐atom catalysts (SACs) mimic the porphyrin molecules and biological enzymes in many catalytic systems due to their high similarity to porphyrin. In contrast, porphyrin‐like single‐atom heterogeneous catalysts possess good recyclability compared with small‐molecule porphyrin homogeneous catalysts. Therefore, as an important family member of SACs, porphyrin‐like SACs are widely studied in various reactions. Herein, the synthesis methods for porphyrin‐like SACs and their applications in many important reactions, including electrochemical reactions and organic synthesis reactions, are summarized. Finally, the challenges and prospects of porphyrin‐like SACs in the further applications are provided. Abstract : Porphyrin‐like single‐atom catalysts (SACs), an important branch of biomimetic catalysts, are extensively explored in many important reactions. Herein, recent progress of these catalysts in the synthesis methods and applications are summarized. Finally, the challenges and prospects of the porphyrin‐like SACs are discussed to offer new insight into this field.